New institutional economics and the analysis of the public sector - Dollery, Brian (2001)
The development of New Institutional Economics (NIE), and especially its core components agency theory, property rights economics and transaction costs economics, appears to have provided policy analysts with powerful tools for the analysis of public sector organisational behaviour and design. In particular, the adoption by NIE of the concept of "bounded rationality" and its employment of a "comparative institutions" approach to the question of economic efficiency seems especially applicable to public bureaucracies. However, NIE is difficult to define with any degree of precision and may well possess an inherent bias towards normative policy prescription favouring market solutions to public sector problems. Reproduced
Keywords: Public sector